Stepping Out - Obele, Cheryl Ann (Macmillan Nigeria Publishers Limited, 1988)
Dr Nweze expected his son to become a doctor too,or perhaps a barrister like his mother.Twelve year old Sunday found it difficult to convince them that he had his own shoes to fill.Then two surprising things happened.
Keywords: Juvenile literature-Fiction; Life Decisions; Realistic